Pengaruh Akuntansi Lingkungan, Kualitas Audit, Dan Keragaman Gender Di Dewan Direksi Terhadap Kinerja Perusahaan Dengan Pengungkapan Keberlanjutan Lingkungan Sebagai Variabel Mediasi - Siti, syerindika_shyati; Agus Munandar, Agus Munandar (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This research was conducted with the aim to determine the effect of environmental accounting, audit quality, and gender diversity on the boardroom, and sustainability disclosures on firm performance as well as the mediating effect of environmental sustainability disclosures on environmental accounting, audit quality, and gender diversity on the boardroom on firm performance in companies banks listed on the Indonesia Stock Exchange in 2018-2021. This research uses the causal step method to determine the effect of each independent variable on the dependent variable and the effect of the mediating variable on other variables. The population in this research was 164 banking companies listed on the Indonesia Stock Exchange for 2018-2021. Furthermore, 30 banking companies were selected for 2018-2021 with a total of 120 research samples selected by the purposive sampling method. The results showed that environmental accounting has an effect on firm performance. Then, the audit quality also has an effect on firm performance. However, the environmental sustainability disclosure has no influential on firm performance as well as the gender diversity on the boardroom which has no positive and significant influential on firm performance. In addition, there is also no influential role played by environmental sustainability disclosures in the relationship between environmental accounting and firm performance, then there is also no influential role played by environmental sustainability disclosures in the correlation between audit quality and firm performance, and there is no influential role that is played by disclosure of environmental sustainability in the correlation between gender diversity on boardroom and firm performance.